2012
DOI: 10.1186/1471-244x-12-147
|View full text |Cite
|
Sign up to set email alerts
|

Disaster exposure as a risk factor for mental health problems, eighteen months, four and ten years post-disaster – a longitudinal study

Abstract: BackgroundDisaster experiences have been associated with higher prevalence rates of (mental) health problems. The objective of this study was to examine the independent relation between a series of single disaster experiences versus the independent predictive value of a accumulation of disaster experiences, i.e. a sum score of experiences and symptoms of distress and post-traumatic stress disorder (PTSD).MethodsSurvivors of a fireworks disaster participated in a longitudinal study and completed a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 35 publications
0
11
1
Order By: Relevance
“…These findings highlight the utility of the ROC approach. A plethora of research has shown that traumatic event incident characteristics, such as degree of property damage (Goenjian et al, 1995; Goenjian et al, 2005; van den Berg, Wong, van der Velden, Boshuizen, & Grievink, 2012), are significantly related to post-disaster mental health symptoms (Goenjian et al, 2001; Parson, Fussell, Rhodes, & Waters, 2012; Zhang, Shi, Wang, & Liu, 2011). The current study suggests that while such disaster incident characteristics may contribute to the etiology and/or maintenance of PTSD per prior research, assessing these variables in post-disaster screenings may not improve prediction of PTSD beyond chance—and other variables are more effective for identifying those at highest risk.…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlight the utility of the ROC approach. A plethora of research has shown that traumatic event incident characteristics, such as degree of property damage (Goenjian et al, 1995; Goenjian et al, 2005; van den Berg, Wong, van der Velden, Boshuizen, & Grievink, 2012), are significantly related to post-disaster mental health symptoms (Goenjian et al, 2001; Parson, Fussell, Rhodes, & Waters, 2012; Zhang, Shi, Wang, & Liu, 2011). The current study suggests that while such disaster incident characteristics may contribute to the etiology and/or maintenance of PTSD per prior research, assessing these variables in post-disaster screenings may not improve prediction of PTSD beyond chance—and other variables are more effective for identifying those at highest risk.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with a previous study reporting an association between home damage and a higher prevalence of depression after a disaster ( Tang et al, 2014 ). Additionally, another study showed that destruction of a home was independently associated with a higher level of PTSD (Posttraumatic Stress Disorder) 18 months after a disaster ( Berg et al, 2012 ). Home damage or destruction could lead to several adversities, including loss of a family member and property, relocation, and lack of a social network, which may cause the observed outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Home damage or destruction could lead to several adversities, including loss of a family member and property, relocation, and lack of a social network, which may cause the observed outcomes. For example, bereavement after natural disasters increases the risk of psychological problems ( Berg et al, 2012 ; Wadworth, DeCarlo Santiago & Einhorn, 2009 ). Female sex predicted increased psychological distress at follow-up in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatrists have a key role, such as caring for the victims and the overall community, in a disaster response [1]. And their activity in disaster is one of the very important factors for recovery [2-4].…”
Section: Introductionmentioning
confidence: 99%
“…And their activity in disaster is one of the very important factors for recovery [2-4]. Volunteer psychiatrists could access mental health problems of survivors of disaster exposure and suggest appropriate interventions shortly after the disaster [1]. After Hurricane Katrina, it showed that the volunteer psychiatrists provided the mental health services and conducted a distinct role of intervening for evacuees [5].…”
Section: Introductionmentioning
confidence: 99%